1984
DOI: 10.1161/01.res.54.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive effect of the GABA receptor agonist muscimol in spontaneously hypertensive rats. Role of the sympathoadrenal axis.

Abstract: The antihypertensive action of central GABA-ergic stimulation was investigated in conscious stroke prone spontaneously hypertensive rats. Injection of the potent GABA agonist muscimol (0.01-1 microgram) into the lateral brain ventricle (icv) lowered mean arterial blood pressure (192.1 +/- 8.4 mm Hg) dose-dependently in stroke prone spontaneously hypertensive rats with a maximal fall of -52.7 +/- 5 mm Hg lasting for about 90 minutes. This was accompanied by bradycardia and sedation. Pretreatment with atropine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…This study demonstrates the profound effect of one of these excitatory inputs, under basal conditions, in anesthetized rats. Considerable experimental evidence implicates altered drive to the sympathetic nervous system from the rostral forebrain in the maintenance of several forms of hypertension, including SH, 8,9,20,21 DOCA salt, 22 and renovascular hypertensive 10,[23][24][25] rats. In this study we demonstrate that the response to removal of the PVN excitatory input is more pronounced in the SHR than in the WKY.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates the profound effect of one of these excitatory inputs, under basal conditions, in anesthetized rats. Considerable experimental evidence implicates altered drive to the sympathetic nervous system from the rostral forebrain in the maintenance of several forms of hypertension, including SH, 8,9,20,21 DOCA salt, 22 and renovascular hypertensive 10,[23][24][25] rats. In this study we demonstrate that the response to removal of the PVN excitatory input is more pronounced in the SHR than in the WKY.…”
Section: Discussionmentioning
confidence: 99%
“…Intraventricular administration of a GABA agonist causes a decrease in arterial pressure by reducing sympathetic nervous system activity. [21][22][23] Most of the response is the result of a hindbrain action, inasmuch as administration of GABA on the ventral surface of the medulla or into the rostral ventrolateral medulla causes profound depressor responses. 24,25 However, a hypothalamic site of action is suggested by GABAergic inhibition of the central angiotensin response 26 and baroreceptor-mediated vasopressin release.…”
Section: Discussionmentioning
confidence: 99%
“…4 It has been shown that spontaneously hypertensive rats (SHR) or stroke-prone SHR (SHRSP) exhibit increased sympathetic activity during development of hypertension and that a positive correlation exists between mean blood pressure and sympathetic nerve activity. [5][6][7][8][9][10] Some studies have also reported that there is a disorder of the L-arginine-NO pathway in SHR and SHRSP. [11][12][13][14] The pressor responses to intravenous administration of the NOS inhibitors N G -nitro-Larginine methyl ester (L-NAME) 11 or N G -monomethyl-Larginine (L-NMMA) 12 have been demonstrated to be smaller in SHR than in WKY.…”
mentioning
confidence: 99%